Danger Signals Activating the Immune Response after Trauma - Stefanie Hirsiger; Hans-Peter Simmen; Clément M. L. Werner; Guido A. Wanner; Daniel Rittirsch (Mediators of Inflammation)
Sterile injury can cause a systemic inflammatory response syndrome (SIRS) that resembles the host response during sepsis. The inflammatory response following trauma comprises various systems of the human body which are cross-linked with each other within a highly complex network of inflammation. Endogenous danger signals (danger-associated molecular patterns; DAMPs; alarmins) as well as exogenous pathogen-associated molecular patterns (PAMPs) play a crucial role in the initiation of the immune response. With popularization of the “danger theory,” numerous DAMPs and PAMPs and their corresponding pathogen-recognition receptors have been identified. In this paper, we highlight the role of the DAMPs high-mobility group box protein 1 (HMGB1), interleukin-1α (IL-1α), and interleukin-33 (IL-33) as unique dual-function mediators as well as mitochondrial danger signals released upon cellular trauma and necrosis.